Spatial-Temporal Adaptive-Order Positivity-Preserving WENO Finite Difference Scheme with Relaxed CFL Condition for Euler Equations with Extreme Conditions (Advances in Applied Mathematics and Mechanics, 2025)
In extreme scenarios, classical high-order WENO schemes may result innon-physical states. The Positivity-Preserving Limiter (PP-Limiter) is often used toensure positivity if CFL≤0.5 with a third-order TVD Runge-Kunta (RK3) scheme.This study proposes two novel conservative WENO-Z methods: AT-PP and AO-PPto improve efficiency with 0.5